Particle swarm optimisation (PSO) algorithm with reduced numberof switches in multilevel inverter (MLI) - Mohammed Rasheed; Rosli Omar; Marizan Sulaiman; Wahidah Abd Halim (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In this work, a three-phase of multilevel inverter (MLI) with reduced number of switches components based on Newton Raphson (NR) and Particle Swarm Optimization (PSO) techniques were presented. The Selective Harmonic Elimination Pulse-Width Modulation (SHE-PWM) is a powerful technique for harmonic minimization in multilevel inverter within allowable limits. NR and PSO techniques were used to determine the switching angles by solving the non-linear equation's analysis of the output voltage waveform of the modified CHB-MLI in order to control the fundamental component. A comparison has been made between NR and PSO techniques related to optimization in order minimize harmonic distortion. The main aims of this paper cover design, modeling, construction the modified topology of the CHB-MLI for a three phase five levels inverter. The controllers based on NR and PSO were applied to the modified multilevel inverter. The inverter offers much less THD using PSO scheme compared with the NR scheme. The performance of the proposed controllers based on NR and PSO techniques done by using MATLAB/Simulink of results are compared.